Pengembangan Home Industry Kuliner Snack Olahan Laut Kabupaten Belitung Dengan Business Model Canvas - Rahmania, Trisna (Politeknik Pariwisata Medan, 2024)
This research aims to find out the condition of the culinary home industry for processed seafood snacks in Belitung Regency; factors that can influence the development of the seafood culinary snack home industry in Belitung Regency; and developing a culinary home industry for processed seafood snacks in Belitung Regency using the BMC (Business Model Canvas) method. The method used in this research is a qualitative descriptive method with data collection techniques through observation, interviews and literature studies with respondents from community-based culinary home industries, MSMEs, cooperatives, as well as domestic and foreign tourists in Belitung using the Business model canvas (BMC). The sampling technique was carried out using non-probability sampling using an incidental technique. The results of the research showed that there were five distribution areas for the Belitung seafood culinary snack home industry with cracker, chips or peanut brittle products. The factors that influence the development of processed seafood snacks are tourist visits, the tourism sector, and transportation, as well as tourist attraction factors based on culinary value, partners, promotions, online media, innovation, and competent people. BMC development is carried out through the identification of nine elements, namely (1) customer segments originating from domestic and foreign countries; (2) the value proposition comes from taste, distinctiveness and uniqueness; (3) key partners are the government, MSMEs, the Hospitality Industry, airlines, culinary entrepreneurs, bloggers and journalists; (4) customer relationships are the attraction of tourists because of promotions, taste, distinctiveness and uniqueness; (5) online media channels; (6) key activities are training, coaching, workshops, FGDs, exhibitions; (7) key resources come from the government, private sector and banking; (8) the cost structure is quite good; and (9) revenue streams contain good appreciation.